PERENCANAAN ULANG GEDUNG KAMPUS MODERN BERBASIS BIM STUDI KASUS GEDUNG FAKULTAS TEKNIK UNIVERSITAS MAJALENGKA - Rahayu, Azi Juliar; Susandi, Dony; Rijaluddin, Arief (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The Faculty of Engineering at Universitas Majalengka currently lacks adequate facilities for its students, particularly laboratory facilities that support practical activities and research. Therefore, a redesign is considered as one of the solutions to transform the Faculty of Engineering building into a campus facility capable of supporting all student activities. This study aims to redesign the Faculty of Engineering building at Universitas Majalengka in accordance with applicable standards, both architecturally using architectural data and structurally using the Special Moment Resisting Frame System (SMRF). The methodology includes space requirement analysis and structural analysis using the response spectrum of Majalengka City. The redesign results in two reinforced concrete buildings, each with five floors. Architectural findings indicate that the space requirement analysis for Building 1 and Building 2 complies with architectural standards. Furthermore, the structural findings show that the displacements in both the X and Y directions for Building 1 and Building 2 remain below the allowable limits, indicating that the planned building structures meet the applicable standards and fall within a safe range.